Sustainable solid waste management measures in Tanzania: An exploratory descriptive case study among vendors at Majengo market in Dodoma City - Nyampundu, Kepha; Mwegoha, William J. S.; Millanzi, Walter C. (BMC Public Health, 2024)
A research article submitted to BMC Public Health 20:1075 of 2020